Perancangan Sistem Pengenalan Rambu-Rambu Lalu Lintas Pada MTS Islamiyah Menggunakan Adobe Flash Prosesional CS6 - Riskawati Riskawati; Zakaria Pratama; Musthafa Haris Munandar; Budianto Bangun (Journal of Student Development Information System (JoSDIS), 2021)
Traffic signs are attributes on the highway that serves to maintain the safety of road users and road equipment, in the form of symbols, letters, numbers, sentences and combinations of them as warnings, prohibitions, commands or instructions for road users. The stages carried out in the design of this application is to collect data using observation techniques, interviews and library data.This technique is done by meeting in person, aiming to obtain complete data. With this application aims to trigger the awareness of MTs Islamiyah students of their own safety and the safety of others on the highway and provide information and understanding of traffic signs into an animated medium of introduction and learning process of traffic well. The results obtained from this application is the design of the system pengenganalan traffic signs based on Adobe Flash Professional CS6.